Correlation Analysis Between Price and Product Completeness With Purchase Decision at Zami Mart - Syamruddin, Syamruddin; Kusuma, Rama Fitradana (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2021)
The purpose of this study was to determine the correlation between price and product completeness with purchasing decisions either partially or simultaneously at Zami Mart, Tangerang. The method used in this research is descriptive quantitative. While the data analysis techniques used in this study are Simple Linear Regression Analysis, Multiple Linear Regression Analysis, Coefficient of Determination Analysis, and Hypothesis Testing (t test and F test). The results showed a correlation between price and product completeness with purchasing decisions. Based on the analysis of the coefficient of determination obtained R Square (R2) = 0.426, where KD = R2 x 100% = 0.426 x 100% = 42.6%. Price and product completeness have a correlation of 42.6% on purchasing decisions, while the remaining 57.4% are influenced by other variables. Furthermore, according to the hypothesis test there is a correlation between price and purchasing decisions where according to the results of the t test, the value of t count > t table (3.999 > 1.98472). Then the completeness of the product has a correlation with purchasing decisions, where according to the results of the t test, the value of t count > t table (3.671 > 1.98472). Furthermore, the price and completeness of the product have a correlation with purchasing decisions. Based on the results of the F test, the calculated F value is greater than F table or 36,011 > 3,090.